Effectiveness Comparison of Activated Carbon/MnO₂ Composite and Mg(OH)₂-Impregnated Activated Carbon as Adsorbents for Uranium Removal from Nuclear Waste : A Review - Artanti Sekarini; Dita Cinta Toharani; Robith Alzamzami; Zidni Aghna Haqina; Hotma Renta (Indonesian Scholar Society, 2026)
Uranium contamination in nuclear wastewater poses significant environmental and health risks due to its radiotoxicity and persistence, necessitating the development of efficient adsorbent materials for its removal. This article discusses the effectiveness of two types of adsorbents: Activated Carbon/MnO2 Composite and Mg(OH)2-Impregnated Activated Carbon, in removing uranium from nuclear waste. Activated carbon/MnO2 composites exhibit high surface area and oxidative properties, enhancing uranium adsorption. In this study, Adsorption isotherm and kinetic analyses revealed that the composite achieved a maximum adsorption capacity of 65.5%, following the Langmuir model and pseudo-second-order kinetics. Meanwhile, Mg(OH)2-Impregnated Activated Carbon enhances the electrostatic interaction between adsorbents and uranium ions, thanks to its alkaline properties that favor the formation of chemical bonds. The maximum adsorption capacity of the predicted Mg(OH)2 reached 85 mg/g, with behavior that was also in accordance with the Langmuir isothermal model. Although both adsorbents show significant potential, the comparison shows that the choice between the two depends on the specific application conditions. The results of this research are expected to contribute to the development of more effective and sustainable nuclear waste management methods, as well as encourage innovation in water purification technology to overcome uranium contamination.